Review of the history, status and prospects of the black tiger shrimp (Penaeus monodon) hatchery sector in Bangladesh - Debnath, P.; Khan, S.H.; Karim, M.; Belton, Ben; Mohan, C.V.; Phillips, M. (Wiley, 2016)
Culture of shrimp, mainly Penaeus monodon, makes an important contribution to Bangladesh's aquaculture industry. Shrimp hatcheries are the foundation on which the shrimp industry is built. Hatchery performance and management therefore has extremely important implications for the long-term viability of the entire shrimp sector, especially given its vulnerability to diseases such as white spot syndrome virus (WSSV). This article provides a review of the history of shrimp hatchery development in Bangladesh and an overview of the current status of the shrimp hatchery sector and the challenges it faces. This article also provides a unique historical analysis of shrimp broodstock performance and rates of WSSV infection using data collected from hatcheries between 2007 and 2013. This reveals sharp declines in broodstock quality and performance over time, and high rates of WSSV infection, with potential major implications for the future sustainability of the sector.